Research on the Impact Mechanism of Digital Inclusive Finance on Enterprise Value - Lombardi, Luca; Ricci, Andrea (Journal of Computer Science and Software Applications, 2026)
The steady enhancement of enterprise value during the development process is of critical importance to firms themselves and also serves as a micro-level foundation for achieving high-quality economic development at the national level. Using A-share listed companies in Shanghai and Shenzhen from 2020 to 2025 as the research sample, this study systematically investigates the impact of digital inclusive finance on enterprise value and its underlying mechanisms. The empirical results indicate that digital inclusive finance significantly promotes enterprise value. Specifically, digital inclusive finance not only enhances enterprise value through two parallel and independent mediating channels-namely increasing R&D investment and promoting substantive innovation-but also improves enterprise value through a chain mediation mechanism in which R&D investment facilitates substantive innovation. The conclusions remain robust after endogeneity treatment and robustness tests. Further heterogeneity analysis reveals that the above impact mechanisms vary across different ownership structures and regional levels of economic development.